Bio-surfactant synthesis from waste cooking oil - Nuredah Aisyah, Nor Azman (2015)
This paper presents the bio-surfactant synthesis from waste cooking oil using alkaline base. Sodium hydroxide will be used as alkaline base. Waste cooking oil is chosen as raw materials in synthesizing bio-surfactant due to fatty acid content and this non-edible oil can be used as an alternative raw. Nowadays, the surfactants mostly made- up from non- renewable sources. The majority of the currently used surfactants are petroleum-based and are produced by chemical means. Waste cooking oils are waste and unuseful material. Making bio-surfactant using waste cooking oil which is inedible vegetables oil versus the human food chain. The mains purpose of this study are to synthesize bio-surfactants from waste cooking oil using base to examine the parameters effect on the bio-surfactant yield. The oil will be added with NaOH and the mixture will be stirred continuously at certain temperature. Then, sulphuric acid and hydrogen peroxide will be added. Several of process temperature, time and concentration of NaOH will be examined. This can improve the yield of bio-surfactant. Furthermore, the process parameter affects the different maximum yield of the bio-surfactants. The resulting bio-surfactant was washed with concentrated sodium chloride, let stand, filtered, washed with distilled water twice and dried in the oven at 60 °C for 24 hours. Then, the characteristic of the bio-surfactant was analyzed and compared with the commercialized detergent. The pH, interaction with hard water, emulsification with oil and height of foam fulfilled the set criteria by ASTM D460.